2010
DOI: 10.1590/s0034-71672010000200026
|View full text |Cite
|
Sign up to set email alerts
|

Dialogando com enfermeiras sobre a avaliação da dor oncológica do paciente sob cuidados paliativos

Abstract: It is an experience report developed next to nurses of a public hospital of Florianópolis-SC, about pain measurement of cancer patient in palliative cares. A total of six nurses had participated of six meeting distributed at three educative moments of this practical. The analysis of undertaken dialogue evidenced that, for the nurses, measurable and objective data are not only enough to measure pain. According to them, it is imperative consider biopsicosociais aspects, valuing integrally the pain that the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 4 publications
(6 reference statements)
0
6
0
7
Order By: Relevance
“…Sometimes, the nurses felt insecure when dealing with the pain and other symptoms of imminent death, resulting in anxiety and doubts regarding the steps to be taken during care-giving. Studies (5,13) have confirmed the necessity of evaluating and interfering in oncologic pain, pointing to the gaps found in the registry, evaluation, systematization and intervention of pain based on specific parameters, because it is seen that, in many cases, the nursing team uses therapeutic and evaluative measures in an empiric and unsystematic format. Many times, such a reality is generated by the unavailability of instruments to evaluate pain, or the lack of trained nursing staff to use them, associated with prejudice regarding the nonstop use of medications with double effects, such as opioids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sometimes, the nurses felt insecure when dealing with the pain and other symptoms of imminent death, resulting in anxiety and doubts regarding the steps to be taken during care-giving. Studies (5,13) have confirmed the necessity of evaluating and interfering in oncologic pain, pointing to the gaps found in the registry, evaluation, systematization and intervention of pain based on specific parameters, because it is seen that, in many cases, the nursing team uses therapeutic and evaluative measures in an empiric and unsystematic format. Many times, such a reality is generated by the unavailability of instruments to evaluate pain, or the lack of trained nursing staff to use them, associated with prejudice regarding the nonstop use of medications with double effects, such as opioids.…”
Section: Discussionmentioning
confidence: 99%
“…From the point of view of both cure and survival, pain management is an important challenge for nurses, because of the difficulties of managing the suffering through pharmaceutical and complementary measures. Among these, we highlight the use of opioids and their derivatives that can generate some uncertainty: for the patients, who fear getting intoxicated and becoming addicted to the drugs, and for the professionals, regarding the best dose that can show sedative or analgesic effects, while avoiding undesirable side effects (5) .…”
Section: In 2008 the International Research Of Cancer Agency Under mentioning
confidence: 99%
See 1 more Smart Citation
“…Por m, foi relatado nos estudos que, para atuar frente a pacientes e familiares que vivenciam o processo de morte e morrer, é necessário uma atuação interdisciplinar. Tal a rmação foi embasada na complexidade do tema o qual envolve dimensões sociais e psicológi-cas Waterkemper, Reibnitz & Monticelli, 2010). Todos os pro ssionais da saúde têm sua responsabilidade frente a pacientes e familiares, incluindo o Enfermeiro (Silva, Campos e Pereira, 2011).…”
Section: Fatores DI Cultantes a Atuação Dos Enfermeirosunclassified
“…Por ser subjetiva e uma experiência individual, é de difícil avaliação e requer dos profissionais suporte educacional, conhecimento e instrumentos que contribuam para sua compreensão (8) . Um dos métodos utilizados para avaliar a dor é a Escala de Avaliação de Sintomas de Edmonton (ESAS), um instrumento que utiliza a combinação de sintomas físicos e psicológicos, composto por nove sintomas frequentemente encontrados em pacientes com câncer (7) .…”
Section: Introductionunclassified